Rad concept: authentic evidence women's specialties in Islamic heritage law - Muhibb Ussabry (Sultang Agung Islamic University, 2020)
Basically, Islam is a religion explains existence of equivalents and parallelization between man and woman which placed woman in a fair position to get her rights in social, economy, politic, and Islamic inheritance law. This study aims to answer gender bias in the manner of describing woman uniqueness in rad concept by Islamic inheritance law. This study uses descriptive-analytic method via normative, juridical, and historical approachment. In jahiliah period, a woman did not get inheritance, even they are commercialized publicly. Islam comes to change that tradition and gives inheritance for her by value a half from man. But, some gender activists argue this statement and say it as discrimination shape for woman, and they disagree with that. This study result shows in rad concept, when there is still treasure rest after be taken by permanent inheritor (aṣhābul furūḍ), according to jumhur ulama that rest is given to all woman inheritors. This proves that Islamic inheritance law comes to glorify woman status and dignity from the beginning till now in giving uniqueness and goodness for woman.